Peran Guru Akidah Akhlak dalam Pembinaan Akhlak Siswi di Era Digital: Studi Kualitatif di SMA Majlis Tafsir Al-Qur’an Surakarta - Sholeh, Makruf Mohammad; Abdullah, Muin (Paedagogie, 2026)
The development of digital technology has brought significant changes to the interaction patterns and behavior of adolescents, including in moral and moral aspects. An open and minimal control digital environment has the potential to affect the formation of students' character, thus demanding the active role of educators in moral development. This study aims to analyze the role of Akidah Akhlak teachers in fostering the morals of female students in the digital era at SMA Majlis Tafsir Al-Qur'an Surakarta. This research uses a qualitative approach with a type of field research. Data was obtained through in-depth interviews, observations, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that Akidah Akhlak teachers play a role as value educators, moral role models, spiritual guides, and social controllers in facing the challenges of the digital era. The coaching strategy is carried out through strengthening moral materials, habituating religious behavior, personal approach to students, and supervision of the use of digital media. Moral development is not only carried out in the classroom, but also through religious activities and character development in the school environment. This research emphasizes that the role of Akidah Akhlak teachers is becoming increasingly strategic in the digital era, because it not only transmits religious knowledge, but also forms moral awareness and character resilience of students in facing social and technological challenges.